Etoposide‐based treatment of adult HLH is associated with high biochemical response but poor survival outcomes. Issue 1 (14th July 2020) - Nicholson, Matthew C.; Naeije, Leonie; Hayden, Anna R.; Mattman, Andre; Dix, David; Chen, Luke Y.C.
Abstract: Etoposide‐based treatment is the standard of care for adult HLH in many centers, yet there remains a paucity of data regarding treatment outcomes. We conducted a retrospective study of 23 adults treated with etoposide‐based therapy compared to 10 pediatric HLH cases at a single center. At diagnosis, the median serum ferritin was 20, 071 µg/L and 937 µg/L in adults and children, respectively; median sIL‐2r was 14, 524 U/mL and 4, 478 U/mL. Biochemical response to treatment was high, with 21/23 adults achieving >75% reduction in serum ferritin, but one year survival was only 7/21 compared to 7/10 in pediatric cases.